Spontaneous open rupture of the Achilles tendon - Lara, Luiz Carlos Ribeiro; Braga Santos, Diego Vitor; Bordignon, Glaucia; Lancia, Lara Furtado; Claudio, Gustavo Kogake; Neves Castanheira, Matheus (Journal of the Foot & Ankle, 2023)
This case report describes a spontaneous open rupture of the Achilles tendon. This type of injury is rare and has few descriptions in the literature. What draws attention in this case report is the extent of the open injury and tendon pullout without associated trauma. This pattern may be related to the patient’s overweight profile and previous history of retrocalcaneal bursitis. The treatment received for the spontaneous open rupture led the patient to a satisfactory result without sequelae.